2014
DOI: 10.1093/rheumatology/keu453
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of histopathological salivary gland biopsy assessment in Sjogren's syndrome: a multicentre cohort study

Abstract: Although FS reliability was good, disparities were noted in the assessment methods used by local pathologists. The protocol for FS determination was not followed routinely, with the result that the FS was often overestimated. Germinal centre-like structures, which predict lymphoma, showed good reliability but were inconsistently reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
0
44
0
2
Order By: Relevance
“…This decision will have an impact on the calculated FS. 16 There was agreement that FS calculation should include the whole of the glandular surface area in the denominator, including abnormal areas, to avoid introduction of bias ( point 7; figure 2B). This includes areas of fibrosis, which cannot reliably be removed from the glandular surface area denominator, although their inclusion may have the potential to reduce the FS, meaning that some patients with a FS ≥1 may become <1 at a late stage of disease (figure 2C).…”
Section: Assessment Of Fls and Fsmentioning
confidence: 90%
See 1 more Smart Citation
“…This decision will have an impact on the calculated FS. 16 There was agreement that FS calculation should include the whole of the glandular surface area in the denominator, including abnormal areas, to avoid introduction of bias ( point 7; figure 2B). This includes areas of fibrosis, which cannot reliably be removed from the glandular surface area denominator, although their inclusion may have the potential to reduce the FS, meaning that some patients with a FS ≥1 may become <1 at a late stage of disease (figure 2C).…”
Section: Assessment Of Fls and Fsmentioning
confidence: 90%
“…NSCS may also be associated with infiltration of lymphocytes and even aggregation, thus raising issues for interpretation and FS calculation. 7 16 The SICCA protocol provides no additional guidance beyond FS calculation on the reporting of size of foci, their degree of organisation, germinal centres (GCs) and lymphoepithelial lesions (LESA), the latter being characterised by lymphocytic infiltration of ducts and basal cell hyperplasia resulting in a multilayered epithelium, and which may also have prognostic significance. 19 The goal of this study was to develop a process of standardisation in order to confirm areas of consensus and highlight areas of uncertainty, with a view to stimulating further research and evidencebased recommendations.…”
Section: And the Proposed American College Of Rheumatology/europeanmentioning
confidence: 99%
“…These data are commensurate with many hospital centres receiving few salivary gland biopsy samples per annum for the investigation of PSS. A recent study from the Tolerance and Efficacy of Rituximab in PSS trial found complete intraobserver agreement for a dichotomised FS (<1 vs ≥1) read 2 months apart by a single specially trained pathologist 52. However, when compared with reports by local pathologists from individual study sites, kappa values were 0.71 for a dichotomised FS, and only 0.46 for determination of FLS.…”
Section: Msg Biopsy As An Outcome Measurementioning
confidence: 98%
“…Histopathological analysis of the salivary glands is examiner-dependent, and assessment of different tissue features may vary significantly between pathologists 15. To circumvent this issue, both our studies used automated methods to analyse immunostained slides and quantify B-cell and T-cell infiltration.…”
mentioning
confidence: 99%